2009
DOI: 10.4067/s0717-95022009000100016
|View full text |Cite
|
Sign up to set email alerts
|

Vas Deferens Surface Epithelium of Agouti paca: Fine Structural Features

Abstract: SUMMARY:The surface epithelium of the vas deferens of Agouti paca, a wild and large South American rodent, was basically formed by principal and basal cells being only the principal cells related to endocytosis processes and also secretion taking base on their cytoplasmic ultrastructural features. Principal cell of vas deferens epithelium were characterized mainly by presence of vesicles with several shapes, sizes and internalized content at their apical cytoplasm occurring smaller pits and pale small vesicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although previous studies on the epididymis of both corresponding species (Alkafafy, 2009;) displayed positive GalTase-IR, the distribution pattern showed interspecies differences. Unlike the buffalo, the cauda epididymidis of the donkey expressed a strong IR suggesting that the distal segments of the male excurrent ducts, including the DD, may present some secretory activities (Manin et al, 1995;Orsi et al, 2009). Contrarily, in human; the GalTase activity was high in the intermediate caput and proximal corpus regions, but maintained low in cauda epididymidis and the vas deferens (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although previous studies on the epididymis of both corresponding species (Alkafafy, 2009;) displayed positive GalTase-IR, the distribution pattern showed interspecies differences. Unlike the buffalo, the cauda epididymidis of the donkey expressed a strong IR suggesting that the distal segments of the male excurrent ducts, including the DD, may present some secretory activities (Manin et al, 1995;Orsi et al, 2009). Contrarily, in human; the GalTase activity was high in the intermediate caput and proximal corpus regions, but maintained low in cauda epididymidis and the vas deferens (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…The ductus deferens (DD) plays a key role in male fertility by providing an appropriate luminal environment for sperm before ejaculation (Hoffer, 1976;Silber, 1989;Carlin et al, 2002; Ductus deferens of donkey & buffalo Alkafafy et al al., 2007;Orsi et al, 2009). Moreover, it was reported that DD has a complex epithelium (Setchell and Brooks, 2006), showing absorptive, synthetic and secretory activities in rodents (Chinoy, 1985;Manin et al, 1995;Orsi et al, 2009) and in humans (Hoffer, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with animals from the Myomorpha suborder, rodent species belonging to the Hystricomorpha suborder have a greater body weight (Table 6). Capybaras and pacas, in particular, are the largest rodents alive (Henrique‐Silva et al, 2007; Orsi et al, 2009). However, except for chinchillas, the ratio between testis mass and body weight (GSI) for this suborder is very low (Table 6), and these 3 rodent species have a monogamous mating system, have longer life spans, produce few litters per year (generally 1–2), and have a spatulate sperm head shape (Eisenberg, 1981; Eddy and O'Brien, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The vas deferens was made up of a pseudo-stratified epithelium, with a layer of connective tissue and a thick muscular layer below, comprised of smooth fibers dispersed within the inner and outer layers [ 50 ]. Principal and basal cells essentially formed the epithelium [ 56 ]. The supranuclear cytoplasm of the principal cells contained numerous lysosomes, adjacent to multi-vesicular bodies with pale or denser content, and endosomes.…”
Section: Paca ( Cuniculus Paca )mentioning
confidence: 99%